2012
DOI: 10.1017/cbo9780511793769
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Struggle, Coexistence, and Democratization in Eastern Europe

Abstract: In societies divided on ethnic and religious lines, problems of democracy are magnified – particularly where groups are mobilized into parties. With the principle of majority rule, minorities should be less willing to endorse democratic institutions where their parties persistently lose elections. While such problems should also hamper transitions to democracy, several diverse Eastern European states have formed democracies even under these conditions. In this book, Sherrill Stroschein argues that sustained pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(28 citation statements)
references
References 226 publications
0
28
0
Order By: Relevance
“…These findings are consistent with earlier studies showing that the outside politics activism of ethnic Hungarians brought delivered positive policies. 124 This study bears theoretical, methodological, and empirical implications. On theoretical grounds, it adds a mediating effect to the relationship between politicization of ethnicity and accommodation of ethnic minorities" rights.…”
Section: Discussionmentioning
confidence: 94%
“…These findings are consistent with earlier studies showing that the outside politics activism of ethnic Hungarians brought delivered positive policies. 124 This study bears theoretical, methodological, and empirical implications. On theoretical grounds, it adds a mediating effect to the relationship between politicization of ethnicity and accommodation of ethnic minorities" rights.…”
Section: Discussionmentioning
confidence: 94%
“…Nonetheless, contestation has remained generally peaceful in CEE. Stroschein has compellingly demonstrated that 'ethnic struggles' in non-violent settings can evolve into forms of deliberation about the meaning of democratic citizenship (Stroschein, 2012). The European framework has provided opportunities for such contestation to change from the zero-sum approach characteristic of traditional nation-state projects to a different understanding of minority mobilization: as contestation about the terms of political inclusion in a multi-ethnic democracy (Salat, 2003).…”
Section: Security Concerns and The Evolving European Minority Regimementioning
confidence: 99%
“…Ethnic parties have become a standard feature of the political landscape in many states, particularly for ethnic minorities. These ethnic parties tend to focus on identity-related issues, such as policies on language use and education, symbols, and increased governance powers for minorities (Horowitz 1985, Stroschein 2001, 2012.…”
Section: B Ethnic Minorities In Democratic Politicsmentioning
confidence: 99%